Pick Up Performance Company Review - Mackrell, Judith (Dance Books Ltd., Alton,Hampshire (UK), 2001)
PALABRAS CLAVE: Pick Up Performance Company, David Gordon, Familiy$Death@Art.COMedy.
Dentro del apartado "Dance Now. Flying High. Dance Umbrella 2001".